107k views
2 votes
Use substitution to write an equivalent quadratic equation.

(3x + 2)2 + 7 (3x + 2) – 8 = 0
-
u2 + 74 - 8 = 0, where u = (3x + 2)2
u2 + 7u - 8 = 0, where u = 3x + 2
u2 + 70 - 8 = 0, where u = 7(3x + 2)
lu² +4-8=0
What’s the answer?

User IcyBrk
by
6.1k points

2 Answers

7 votes

Answer:

second option:
u^(2)+7u-8=0

Explanation:

We have the equation given:


(3x+2)^(2)+7(3x+2)-8=0

We can replace the variable in the quardatic equation.

So,


Putting\\u=3x+2

Putting u in place of 3x+2 will give us:


(u)^(2)+7(u)-8=0

So the answer is:


u^(2)+7u-8=0

So, the second option is correct ..

User Irem
by
5.7k points
4 votes

For this case we can make a change of variable, to obtain a quadratic equation of the form:


ax ^ 2 + bx + c = 0

Making the change:
u = 3x + 2

Substituting the change we have:


u ^ 2 + 7u-8 = 0

Thus, the correct option is:
u ^ 2 + 7u-8 = 0where
u = 3x + 2

Answer:

Option B